2020
DOI: 10.1021/acsami.0c10332
|View full text |Cite
|
Sign up to set email alerts
|

Phosphonic Acid Modified ZnO Nanowire Sensors: Directing Reaction Pathway of Volatile Carbonyl Compounds

Abstract: Surface molecular transformations on nanoscale metal oxides are inherently complex, and directing those reaction pathways is still challenging but important for designing their various applications, including molecular sensing, catalysts, and others. Here, a rational strategy to direct a reaction pathway of volatile carbonyl compounds (nonanal: biomarker) on single-crystalline ZnO nanowire surfaces via molecular modification is demonstrated. The introduction of a methylphosphonic acid modification on the ZnO n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 48 publications
1
19
0
Order By: Relevance
“…Other groups have identified alternative reactions for which organic ligands can influence catalysis on oxides; these have particularly focused on selective site poisoning. For example, PA SAMs have been used to suppress undesired reactions on ZnO nanowires for sensor applications . In that case, the modifiers diminish the availability of adjacent sites needed for bimolecular aldol condensation reactions of aldehydes while still permitting aldehyde adsorption at significant coverages.…”
Section: Organic Modification Of Metal Oxide Catalystsmentioning
confidence: 99%
“…Other groups have identified alternative reactions for which organic ligands can influence catalysis on oxides; these have particularly focused on selective site poisoning. For example, PA SAMs have been used to suppress undesired reactions on ZnO nanowires for sensor applications . In that case, the modifiers diminish the availability of adjacent sites needed for bimolecular aldol condensation reactions of aldehydes while still permitting aldehyde adsorption at significant coverages.…”
Section: Organic Modification Of Metal Oxide Catalystsmentioning
confidence: 99%
“…For example, self-assembled monolayers (SAMs) deposited from various precursors, such as thiols or amines, have been used to crowd the surface of metal catalyst particles in order to improve reactivity through steric and/or electronic effects. ,, Additionally, it has been shown that modifiers can be specifically designed to take advantage of π–π interactions between an aromatic reactant and modifier, leading to significantly higher yield in the selective hydrogenation of cinnamaldehyde . More recent work has explored the use of phosphonic acids (PAs) as surface modifiers, which typically deposit onto metal oxide catalysts and supports. These studies have found that PA modifiers can enhance catalyst behavior by providing steric effects, improving catalyst stability, introducing additional active sites, or promoting the adsorption and subsequent reaction of an adsorbate. , Moreover, organic PA modifiers have been shown to be surprisingly stable (to >300 °C) under high-temperature hydrogenation conditions . They are also stable under hydrothermal conditions, though oxidizing conditions are known to degrade the organic ligands at temperatures near 200 °C. , …”
Section: Introductionmentioning
confidence: 99%
“…[26][27][28][29][30] For example, a ZnO NW semiconductor-based electrical sensor was fabricated to detect nonanal, a biomarker for lung cancer. 31 In addition, biomolecular analysis systems based on specic interactions with biomolecules have been constructed using ZnO NWs. Examples include a highly sensitive and selective ZnO NW sensor for immunoglobulin G 32 and a ZnO NW microuidic device to detect cancer-related miRNA biomarkers from urinary extracellular vesicles.…”
Section: Introductionmentioning
confidence: 99%